Decision Support System for Determining Doctoral Scholarship Recipients at STMIK Pelita Nusantara with the Topsis Method - Erlinda Hutagaol (International Journal of Basic and Applied Science, 2020)
This research is a decision support system for determining S3 scholarship recipients at STMIK Pelita Nusantara with TOPSIS method. The TOPSIS method is used for determining S3 scholarship recipients that are determined based on criteria. This decision support system was built with Visual Studio 2010 application as a tool for determining S3 scholarship recipients at STMIK Pelita Nusantara and using MYSQL as a database. The result of this decision support system is to produce an objective and systematic decision support system in determining the S3 scholarship recipients with the best qualifications. This system aims to help the foundation in selecting lecturers who are eligible to get a S3 scholarship at STMIK Pelita Nusantara.